2007
DOI: 10.1159/000109811
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging and Correlates of Cognitive Function among Patients with Heart Failure

Abstract: Background/Aims: We purposed to investigate the relationship between cerebral abnormalities detected by magnetic resonance imaging (MRI) and cognitive performance in nondemented outpatients with heart failure (HF). Methods: In 58 patients with HF neuropsychological assessment was performed including tests of mental speed, executive functions, memory, language and visuospatial functions. Deep, periventricular and total white matter hyperintensities (WMH), lacunar and cortical infarcts, global and medial tempora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
84
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(92 citation statements)
references
References 62 publications
4
84
0
4
Order By: Relevance
“…131,132 Energy depletion is associated with decreased brain size, 133 and in patients with cardiac failure medial temporal lobe atrophy, but not T2 white matter hyperintensities, it is associated with hypotension 134 and impaired cognitive functioning. 135 Furthermore, in a large prospective study in patients with chronic obstructive pulmonary disease, hypoxemia was the only parameter associated with the occurrence of cognitive failure after multivariable regression analysis and treatment with supplemental oxygen decreased the risk 136 matching functional damage without structural lesions.…”
Section: Discussionmentioning
confidence: 99%
“…131,132 Energy depletion is associated with decreased brain size, 133 and in patients with cardiac failure medial temporal lobe atrophy, but not T2 white matter hyperintensities, it is associated with hypotension 134 and impaired cognitive functioning. 135 Furthermore, in a large prospective study in patients with chronic obstructive pulmonary disease, hypoxemia was the only parameter associated with the occurrence of cognitive failure after multivariable regression analysis and treatment with supplemental oxygen decreased the risk 136 matching functional damage without structural lesions.…”
Section: Discussionmentioning
confidence: 99%
“…39 Cerebral abnormalities detected on magnetic resonance imaging and cognitive performance in HF patients have been reported. 40 For instance, medial temporal lobe atrophy was related to cognitive dysfunction, involving memory impairment and executive dysfunction, whereas total white matter hyperintensities were related to depression resulting in insomnia. 40 To date, there are no data on effective treatment for insomnia in HF patients.…”
Section: Discussionmentioning
confidence: 99%
“…40 For instance, medial temporal lobe atrophy was related to cognitive dysfunction, involving memory impairment and executive dysfunction, whereas total white matter hyperintensities were related to depression resulting in insomnia. 40 To date, there are no data on effective treatment for insomnia in HF patients. General behavioral measures for improved sleep hygiene, such as minimal use of caffeine, cigarettes and alcohol, maintaining a regular sleep schedule, going to bed only when sleepy, regular exercise, and avoiding daytime naps, should be explained to the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Pooled analysis of 22 case-control studies investigating cognitive function in CHF patients demonstrated an odds ratio of 1.62 (P < 0.0001) for cognitive impairment in patients with CHF [139]. Neuroimaging studies have shown evidence of structural alteration of brain associated with heart failure.…”
Section: Cognitive Dysfunctionmentioning
confidence: 99%